Skin diseases seen in the elderly patients - Kökçam, Ibrahim; Dilek, Nursel (My University, 2007)
Introduction: There are limited numbers of investigations associated with the skin diseases and their prevalence in the elderly people. In the present study, we aimed to determine the skin diseases and their prevalence in this group of people in our region. Materials and Method: The registry records of 270 patients at the ages of 60 years and over admitted to the dermatology outpatient clinic behveen January 2005 ano January 2007 were retrospectively investigated in terms of age, sex, findings from dermatological examination and diagnosis. Results: Of 270, 148 (54.8%) of the patients were male and 122 (45.2%) were female. Patients were classified into 8 different groups in terms of types of their cutaneous diseases. Infectious skin diseases (29.6%), immunological skin diseases (24.8%), and inflammatory skin diseases were the most frequently seen dermatological diseases. Skin tumors (11.8%), pruritus, (7.5%), infestations (2.6%), dermatoses induced by UV (2.6%) and other diseases (5.9%) were also diagnosed. Conclusion: In the present study, infectious skin diseases, immunological and inflammatory skin diseases were the most frequently seen groups of skin diseases in the elderly people in. in our region. These diseases usually affect quality of life negatively in this group of people.
Yaşli hastalarda görülen deri?hastaliklari
Keywords: Elderly; Patient; Skin diseases